Pengaruh Pembelajaran Kooperatif Tipe Make A Match Terhadap Peningkatan Hasil Belajar Matematika Siswa Barru - Nusriana Nur'eni; Hastuty Musa; Asdar Dollo (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2023)
This study aims to find out that the make a match type learning model has a positive effect on improving mathematics learning outcomes of barru district students. The type of research used is a type of experimental research. The variables studied in this study were the mathematics learning outcomes of barru district students. The population of this study were all students of barru district students for the 2023 academic year consisting of five classes.Sampling used cluster random sampling technique, one class was taken from five classes by lottery, namely class VII.2. The instrument used in this study was a validated learning outcomes test. The results showed that there was an increase in students mathematics learning outcomes, based on descriptive statistical analysis the average value of mathematics learning outcomes was obtained before applying the make a match type learning model, namely 45.85, the average value of mathematics learning outcomes after applying the make a match type learning model is match is 72.07 and the average value of the gain is 0.46. Based on the inferential statistical analysis using the One Sample t-test, a significant value was obtained, p = 0.026 < a = 0.05, this means that H0 is rejected and H1 is accepted. So it can be concluded that there is a positive influence of the make a match type learning model on the learning outcomes of barru district students.